Survival and redox activity of Friedmanniomyces endolithicus, an Antarctic endemic black meristematic fungus, after gamma rays exposure. Issue 12 (December 2018) - Pacelli, Claudia; Bryan, Ruth A.; Onofri, Silvano; Selbmann, Laura; Zucconi, Laura; Shuryak, Igor; Dadachova, Ekaterina
Abstract: Despite living organisms are not exposed to acute ionizing radiation under natural conditions, some exhibit a high radiation resistance. Understanding this phenomenon is important for assessing the impact of radiation-related accidents, occupational exposures and space missions. In this context, in this study we analyzed the effect of gamma rays on the Antarctic cryptoendolithic melanized fungus Friedmanniomyces endolithicus CCFEE 5208 and demonstrated its resistance to acute doses of gamma radiation (up to 400 Gy), accompanied by increase in metabolic activity.